2006
DOI: 10.1016/s0022-5347(06)00600-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cosmetic and Sexual Outcome of Hypospadias Surgery: Norm Related Study in Adolescence

Abstract: Although patients with hypospadias had a slightly higher rate of dissatisfaction with penile size, their sexual behavior was not different from that in control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 18 publications
9
49
0
1
Order By: Relevance
“…As a successful plastic surgery for hypospadias, not only the normal position of meatus should be reconstructed, but also the physical and psychological impact of penile appearance on patients after surgery should be considered. In our series, smaller penile size was the main reason for dissatisfaction with penile appearance and for improvement on cosmesis, which is similar to the reports of several other authors [6,10,17]. Mureau et al [5] also mentioned that patients are less satisfied with penile size than surgeon are.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a successful plastic surgery for hypospadias, not only the normal position of meatus should be reconstructed, but also the physical and psychological impact of penile appearance on patients after surgery should be considered. In our series, smaller penile size was the main reason for dissatisfaction with penile appearance and for improvement on cosmesis, which is similar to the reports of several other authors [6,10,17]. Mureau et al [5] also mentioned that patients are less satisfied with penile size than surgeon are.…”
Section: Discussionsupporting
confidence: 90%
“…When contacted directly with doctors, patients may not provide frank answers because of certain considerations or fears [17]. And we also believe that the best judge of the long-term success of hypospadias repairs is the patient himself, who can best assess functional outcomes and satisfaction [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, we may assume that a self-administered questionnaire would be a better method to elicit reliable answers than a direct interview for such delicate and personal matters. When contacted directly with doctors, patients may not provide frank answers because of certain assumptions or fears [22] .…”
Section: Discussionmentioning
confidence: 99%
“…While some contemporary studies showed significant differences between former hypospadias patients and controls concerning frequency of sexual activity, masturbation, orgasmic function and overall sexual satisfaction, other recent studies failed to show significant differences in sexual behavior patterns. 28,29 It seems that there is no clear cut answer as to the effects of prior hypospadias surgery on adult sexual function. This is probably due to the multi-factorial nature of the question at hand.…”
Section: Sexual Function In Adults Who Have Previously Undergone Hypmentioning
confidence: 99%